A Deep Neural Network for Simultaneous Estimation of b Jet Energy and Resolution; Computing and Software for Big Science; Vol. 2020, iss. 4 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich (2020, 2020)
Title screen